Hubungan Antara Perceived Organizational Support Dengan Readiness for Change Pada Karyawan BRI Di Banda Aceh - Firas Mahdani; Elida Syahriati; Mirza Mirza; Eka Dian Aprilia (IJIP : Indonesian Journal of Islamic Psychology, 2022)
Abstract Aceh Banking must have sharia status (Aceh Qanun No. 11/2018). It has affected BRI in Banda Aceh. The research purpose is to see the relationship between Perceived Organizational Support (POS) and Readiness for Change (RfC) for BRI employees in Banda Aceh. The method is quantitative (198 BRI employees) and the sampling type is simple random sampling (87 men and 111 women). POS scale, Survey POS, and RfC scale as measuring tools. SBF correlation analysis shows that there is a positive relationship between PSO and RfC for BRI employees in Banda Aceh. Conversely, the lower the PSO, the lower the RfC. Keywords: perceived organizational support; readiness for change; employee of BRI  AbstrakPerbankan di Aceh wajib berstatus syariah (Qanun Aceh No. 11/2018). Peraturan ini berdampak pada BRI di Banda Aceh. Tujuan penelitian, melihat hubungan antara Perceived Organizational Support (POS) dengan Readiness for Change (RfC) pada karyawan BRI di Banda Aceh. Metodenya kuantitatif (198 karyawan BRI di Banda Aceh) dan jenis samplingnya simple random sampling (87 pria dan 111 wanita). Skala POS, Survey POS, dan skala RfC sebagai alat ukurnya. Dari analisis korelasi Spearman Brown Formula (SBF), menunjukkan terdapat hubungan positif antara PSO dengan RfC pada karyawan BRI di Banda Aceh. Sebaliknya, semakin rendah PSO, maka semakin rendah RfC-nya.Kata Kunci: perceived organizational support; readiness for change; karyawan BRI